Why read Moby-Dick? [compact disc, unabridged] - Philbrick, Nathaniel (Penguin Audio, 2011)
Shares expert guidelines on how to read and appreciate Herman Melville's classic work, offering insight into its history, characters, and themes while explaining its literary relevance in the modern world.